CTIM-07. IDENTIFICATION OF A BASELINE BIOMARKER ASSOCIATED WITH TUMOR RESPONSES IN A PHASE I/IIa TRIAL OF A THERAPEUTIC CMV VACCINE AGAINST RECURRENT GLIOBLASTOMA (GBM). (9th November 2020) - Wen, Patrick; Reardon, David; Forst, Deborah; Lee, Eudocia; Iwamoto, Fabio; Diaz-Mitoma, Francisco; Anderson, David; Lassman, Andrew
Abstract: Cytomegalovirus (CMV) antigens have been reported in over 90% of GBM tumors. CD4 + and CD8 + T cells are most frequently directed against the gB and pp65 antigens, respectively, and are immunogenic targets in a CMV-based GBM vaccine. We enrolled 10 patients (6 women, 4 men) with KPS at least 70 and first recurrence of GBM to a trial (Phase IIa extension) of gB/pp65 enveloped virus-like particles (eVLPs) with GM-CSF. Intradermal vaccination was administered every 4 weeks, with serologic immune-monitoring 2 weeks after each vaccination and surveillance brain MRI scans every 6 weeks. Median age was 59 years (range 33–67). Among 8 response-evaluable patients, we observed 1 SD and 1 PR. Among all patients treated on phase I and II (n=26), a normal baseline ratio of CD4/CD8 T cells in peripheral blood predicted response (n=6). Other baseline peripheral blood markers did not correlate with efficacy, including total white blood cell, lymphocyte percentage, and absolute lymphocyte count. During treatment, the peripheral blood of responders demonstrated dynamic losses followed by subsequent reappearance and expansion of CMV-specific CD4+ effector memory T cells. Based on these encouraging results, a new arm is enrolling subjects combining gB/pp65 eVLPs (at the same dose) formulated with adjuvant intramuscular AS01B and results will be presented.